Manajemen Pimpinan dalam Menanggulangi Tindakan Bullying di Pondok Pesantren Minhajus Sunnah Pulo Bargot Labura - Azlisa Azlisa; Tengku Walisyah (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Leadership management in overcoming actions that damage the good image of Islamic boarding schools and seeing the rise in cases of bullying in the world of education today and especially in the Islamic boarding school environment. The method used in this research is a qualitative method with a field research approach using observational data collection techniques from leaders regarding the countermeasures carried out at the Minhajus Sunnah Pulo Bargot Islamic Boarding School, followed by interviews with the head of the Islamic boarding school and related staff and documentation through references and literature. related to research. This research is guided by the theory of George R. Terry, namely POAC as a research analysis tool. The results of this research show that a leader is essentially one who is able to influence other people with criteria, appearance and with his power, the results of the discussion regarding leadership planning regarding the cultivation of morals and etiquette in muhadhoroh activities, selecting quality teachers and providing martial arts extracurriculars, and in organizing, placing staff according to the skills they are pursuing and actuating regarding the leadership continuing to strive to maintain defense from planning and organizing that has been determined and finally controlling the results that have been carried out.